Spontaneous Pneumomediastinum from Running Sprints - Joseph W. Turban (Case Reports in Medicine)
Spontaneous pneumomediastinum (SPM) is a fairly rare condition, caused by increased intrathoracic pressure, leading to free air in the mediastinal structures. Underlying lung conditions are associated with increased incidence of SPM, including asthma, interstitial lung disease, pneumonia, bullous lung, and radiation therapy for lung cancer. It is often preceded by Valsalva maneuvers, vomiting, coughing, asthma exacerbation, sneezing, childbirth, or intense physical activity. A case of SPM is presented in a 15-year-old male, who complained of throat pain and dyspnea while running sprints at football practice. Workup revealed SPM, and he was subsequently admitted and treated conservatively. His symptoms resolved in 2 days and he was discharged and suffered no further recurrences. In contrast to secondary pneumomediastinum, SPM is usually a benign condition although life-threatening conditions can rarely arise. Differentiating between these two conditions has important prognostic indications. There is a paucity of prospectively collected data regarding SPM, and considerable variation in recommendations concerning the extent of workup.